Development of Domino Card Learning Media for Puppet Stories on the Competence of Understanding the Content of the Text of the Ramayana Puppet Story (Resi Jatayu) Grade VIII Junior High School - Riko Andrianto; Agus Yuwono (Journal of Social Research, 2025)
The research was motivated by the fact that many grade VIII students of SMP Negeri 1 Juwiring still have difficulty understanding the content of the text in the Resi Jatayu story, as well as by the lack of learning media, which leads to monotonous learning. This research aims to develop learning media in the form of domino card puppet stories to improve learning outcomes and understanding of the content of the text of the Ramayana story (Resi Jatayu). The research method uses the Research and Development (R&D) approach. The data collection techniques used were a needs questionnaire, interviews, and a validation test questionnaire. The data analysis employed is qualitative descriptive data analysis. The results of this study produced a domino card learning media for puppet stories based on the analysis of students’ needs. It was designed using the Adobe Illustrator application, resulting in 40 domino card designs that include pictures, story excerpts, practice questions, and are accompanied by a guidebook. Based on the media feasibility category, the domino card material validation test obtained a result of 91.67%, which is included in the "very feasible" category. Meanwhile, from the results of the domino card media validation test, a result of 87.5% was obtained, which was also included in the "very feasible" category.